Learning Autonomy: A Way to Improve English Language Teaching (ELT) in Indonesia - Suharmanto Suharmanto (TEFLIN, 2003)
In Indonesia English is the first foreign language and taught as a comÃÂpulsory subject in secondary and tertiary education with the objective primarily to provide the students with the ability to read English textbooks on their related fields. In spite of the efÃÂforts made to improve the teaching especially in secondary school, the reÃÂsult is, so far, still unsatisfactory. This article argues that the implementation of learning autonomy could possibly be a way to improve ELT in Indonesia.